2021
DOI: 10.1111/mec.16242
|View full text |Cite
|
Sign up to set email alerts
|

Disturbance alters the forest soil microbiome

Abstract: In the current period of rapid, global, environmental change, forest ecosystems face many compounding and interacting challenges

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 129 publications
1
23
0
Order By: Relevance
“…Associations between microbial communities and fire (Dooley & Treseder, 2012; Holden et al, 2013, 2016) and between microbial communities and biotic and abiotic properties (Bowd et al, 2022; Tedersoo et al, 2014; Wardle & Jonsson, 2014) have been well‐documented, although their capacity to interact and influence these communities are seldom investigated (Bowd, Banks, et al, 2021). Despite this, it is widely recognised that fire is a key regulator of plant communities (Foster et al, 2018; Tepley et al, 2018) and nutrient cycles, and influences the input (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Associations between microbial communities and fire (Dooley & Treseder, 2012; Holden et al, 2013, 2016) and between microbial communities and biotic and abiotic properties (Bowd et al, 2022; Tedersoo et al, 2014; Wardle & Jonsson, 2014) have been well‐documented, although their capacity to interact and influence these communities are seldom investigated (Bowd, Banks, et al, 2021). Despite this, it is widely recognised that fire is a key regulator of plant communities (Foster et al, 2018; Tepley et al, 2018) and nutrient cycles, and influences the input (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these research questions, we constructed three hypotheses that are outlined below.Hypothesis Fire will influence microbial communities both directly and indirectly through interactions with plants, microbes and abiotic properties. This is because while microbial communities may be sensitive to direct fire effects (via fire‐induced mortality) (Bååth et al, 1995; Glassman et al, 2016), they also have well‐known associations with abiotic and biotic properties (Bowd et al., 2022; Tedersoo et al, 2014; Wardle & Jonsson, 2014) that can also be altered by fire (Bowd, Banks, et al, 2021; Butler et al., 2019; Foster et al, 2017; Pellegrini et al, 2018). Hypothesis Direct and indirect fire effects will vary within and between microbial communities and groups, likely reflecting species‐specific physiological and ecological differences, disturbance tolerances and specific functional roles (Bååth et al, 1995; Sun et al, 2015; Voriskova & Baldrian, 2013; Wardle & Jonsson, 2014; Waring et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar increases in disease incidence have been observed in plantations in Tasmania that were established on sites previously occupied by natural forests (Carnegie, 2007). A recent study demonstrated that forest disturbances alter the diversity and composition of the soil microbiome (Bowd et al, 2021). For example, the diversity of saprotrophic fungi was positively associated with the number of fire events.…”
Section: Discussionmentioning
confidence: 99%
“…Microbial biomass is characteristically lowered following a wildfire [8,9], and recovery of soil communities may span decades [9]. Microbial diversity would be expected to decline with the number of fires, as noted by Bowd et al [10]. However, soil erodibility is enhanced post-fire [11], which would aid in the dispersal of organisms.…”
Section: Introductionmentioning
confidence: 94%